Male uav longitudinal stability determination using wind tunnel data - Adhynugraha, Muhammad Ilham; Megawanto, Fadli Cahya; Octaviany, Siti Vivi; Budiarti, Dewi Habsari; Muliadi, Jemie; Nami, Osen Fili; Wibowo, Singgih Satrio (Jurnal Teknosains, 2024)
Unmanned aerial systems have been increasing in demand for a wide range of operations, including the rapid growth of advanced navigation and communication. One of the most important things in designing an Unmanned Aerial System (UAS) is to ensure the system's stability, such as the UAS itself. This study was conducted on an in-house medium altitude long endurance (MALE) UAS aircraft. It is focused on analyzing the longitudinal stability of MALE UAS. A mathematical approach was used to analyze the longitudinal stability.  A series of wind tunnel tests using a scaled model of the MALE UAS is done to produce several sets of data containing longitudinal stability derivatives for various configurations. A few sets of data are chosen to obtain the stability derivatives needed. These stability derivatives are utilized to determine the longitudinal motion characteristic of the aircraft. The analysis of certain derivatives and the phugoid and short-period mode shows that the aircraft is statically and dynamically stable in longitudinal motion. The results indicated that a weight change prompted an altercation in the natural frequency of the short-period mode. The response also showed that reaching a new equilibrium state takes a rather long period after an arbitrary perturbation is initiated. The time required to subdue oscillation in axial and average velocities is more than 100 seconds. The stability in the pitch rate is reached in around 65 seconds. The time to reach stability in pitch angle response is around 65 seconds.